THE STRUCTURAL TRANSFER AT THE SOUTHERN END OF TALAS-FERGHANA FAULT AND ITS REGIONAL TECTONIC RESPONSE IN THE CENOZOIC - Li J.; Geng Y.; Cai Z.; Luo C. (My University, 2007)
Talas-Ferghana fault (TF) is is a major right-lateral strike-slip fault in the central Asia. One unresolved issue is the its southward extension and propagation across the Tarim basin. Based on remote sensing geology, field observation and and geophysical survey, it is suggested that the Cenozoic TF terminated in the Kashi depression (KD) by minor dextral strike-slip faults. The dextral shearing along TF is accommodated by thrusting systems at its eastern block, which resulted in contrasting structures on the both sides of TF in the western Tarim basin. The Kashi depression located between the Pamir and TF is a foreland basin filled by thick Cenozoic molasses sequence. With the northward thrusting of Pamir, a series of E-W to NW folds and thrusting faults developed in the Mesozoic to Cenozoic sequences. With the blocking of Bachu uplift, the dextral shearing with TF is transfered into horizontal shortening along Keping thrust belt to the east. Regional tectonic analysis indicates that the northward thrusting of Pamir plateau has reactivated TF in the Late Cenozoic, with dextral shearing and structural transferring. As a result, The pamir show asymmetric structural pattern on its both sides.
Keywords: CENOZOIC; CENTRAL ASIA; DEXTRAL SHEARING; FORELAND BASIN; THRUSTING SYSTEM